Critical experimental evaluation of hydrogen blends with conventional fuels for enhanced power generator performance - Erdemir, Dogan; Dincer, Ibrahim; Patel, Dipal (ELSEVIER SCI LTD, 2025)
This experimental work explores the use of hydrogen blends with gasoline, methane, and propane in power generators. A commercial gasoline engine-driven stationary power generator with a capacity of 3.65 kW is utilized during the tests. A dual-fuel carburetor is included in the engine to adjust the desired fuel mixture after a set of modifications. Gasoline, methane, and propane are then blended volumetrically with hydrogen with the ratios of 5 %, 10 %, 15 %, and 20 %. The tests with 100 % gasoline, methane, and propane are also conducted to make a proper comparison. The power output of the generator, temperature at the cylinder exit, and exhaust gases are experimentally tested, and the obtained measurements are then analyzed. The results reveal that increasing hydrogen content up to 20 % significantly has reduced CO2 emissions by 42.8 % for gasoline, 46.9 % for propane, and 37.7 % for methane, while also reducing CO emissions by 44.8 %, 50 %, and 40 % for gasoline, propane, and methane, respectively. However, NOx emissions tend to increase significantly with hydrogen addition, particularly for propane (186.3 % increase) and methane (154.8 % increase). The power output of the generator and efficiency generally improved, with propane showing the highest increase in power (10 %) and methane exhibiting the most significant gain in efficiency (reaching parity with gasoline at 20 % hydrogen). With increasing hydrogen content, the operating cost per hour has decreased for all fuel types.
Keywords: Fuel; Fuel blends; Hydrogen; Hydrogen blends; Power generator; Emissions; Environmental impact; Sustainability; DIRECT-INJECTION ENGINE; NATURAL-GAS; EMISSIONS CHARACTERISTICS; COMBUSTION BEHAVIORS; IGNITION ENGINE; Energy & Fuels; Engineering